Bioremediation of heavy metals using microalgae: Recent advances and mechanisms - Leong, Yoong Kit; Chang, Jo-Shu (Bioresource technology, 2020)
•Bioremediation of five toxic heavy metals by microalgae were reviewed in-depth.•Feasibility and potential of value-added product accumulation were evaluated.•Discussion of advanced techniques and integration with other technologies.•Challenges and proposed strategies were summarized along with future prospects. Five heavy metals namely, arsenic (As), cadmium (Cd), chromium (Cr), lead (Pb) and mercury (Hg) are carcinogenic and show toxicity even at trace amounts, posing threats to environmental ecology and human health. There is an emerging trend of employing microalgae in phycoremediation of heavy metals, due to several benefits including abundant availability, inexpensive, excellent metal removal efficiency and eco-friendly nature. This review presents the recent advances and mechanisms involved in bioremediation and biosorption of these toxic heavy metals utilizing microalgae. Tolerance and response of different microalgae strains to heavy metals and their bioaccumulation capability with value-added by-products formation as well as utilization of non-living biomass as biosorbents are discussed. Furthermore, challenges and future prospects in bioremediation of heavy metals by microalgae are also explored. This review aims to provide useful insights to help future development of efficient and commercially viable technology for microalgae-based heavy metal bioremediation.